Development of Adventure-Based Guidance To Improve Self-Management of High School Students - Ambarwati; Farozin, Muh (Psikopedagogia, 2024)
This development study aims to create adventure-based guidance services to enhance students' self-management and to determine the feasibility, practicality, and effectiveness of these services. The development model used is the 4-D model. The selection of subjects was conducted using a random sampling technique. The research subjects consisted of 36 students in the experimental group and 36 students in the control group. The data collection technique involved the use of a questionnaire. Data analysis to determine product effectiveness was conducted using a paired-sample t-test. The results of this study indicate that: (1) The feasibility of adventure-based guidance services, based on validation scores from material experts, falls into the "feasible" category, while validation from media experts falls into the "very feasible" category. (2) Practicality, based on user validation results, is categorized as "very feasible." (3) The effectiveness of adventure-based guidance services in improving high school students' self-management, as measured by pre-test and post-test results, showed an increase from 26.56 to 72.89. This demonstrates an improvement in student self-management, indicating that the developed services are effective. Guidance and counseling teachers can utilize the results of this study to help students enhance their self-management through adventure-based guidance.